Regulatory Role of Gender in the Effect of Outdoor Recreation Self-Efficacy on the Recreational Risk-taking Behavior - Tez, Özge Yavaş; Gürbüz, Pınar Güzel; Esentaş, Melike (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2021)
The study aims to reveal whether the gender variable has a regulatory role in the effect of self-efficacy of outdoor recreational events participated by individuals on recreational risk-taking behavior. The sample group of the study consisted of 370 leisure time participants who participated in different outdoor recreation activities. Personal information form, Outdoor Recreation Self-Efficacy (ORSE), and A-Domain-Specific Risk-Taking Scale Short Form (DOSPERT) were applied to the participants in the study. It has been found following the analysis that there is a causal relationship between outdoor recreation self-efficacy and recreational risk-taking behavior and the p-value is statistically significant. After the regulatory impact analysis, significant differences were found in the relation “outdoor recreation self-efficacy and recreational risk-taking behavior” (β=.39 in female and β=.38 in male for skill and efficacy and recreational risk-taking, p< 0.001; β=.41 in female and β=.34 in male for achievement and pleasure and recreational risk-taking, p< 0.001)